Climate change, pharmaceuticals and prescribing patterns: a scoping review and proposal for the MAMS model for healthcare educators - Kenneth Mueller; Heather Allstrom; Nina Ali; Sharon Leslie; Lori Modly; Joseph Crane; Rebecca Philipsborn; Daniel Jackson Smith (Frontiers in Public Health, 2026)
Background Healthcare contributes substantially to climate change, and pharmaceuticals account for a meaningful share of this footprint across manufacturing, distribution, prescribing, and disposal. However, climate-health education and prescribing practices are often addressed separately, leaving limited guidance for integrating climate change, pharmaceuticals, and prescribing patterns within a single framework. This scoping review synthesizes evidence on the intersection of these domains, with attention to how these concepts are incorporated into health professions education (HPE) and clinical practice. Methods A comprehensive literature search strategy of six databases (PubMed, Embase, CINAHL, ERIC, Health Source: Nursing Academic, and Web of Science) identified peer-reviewed studies published between January 1988 and December 2025 in English or Spanish. Eligible studies addressed climate change in relation to pharmaceutical use or prescribing patterns and included an educational or practice-based component; animal studies, studies without interventions, and non-prescribing studies were excluded. Searches were conducted in December 2023 and updated in April 2025. Data were extracted on study characteristics, clinical domain, educational approach, and directional relationships mapped to the MAMS model dyads (Climate ↔ pharmaceuticals; pharmaceuticals ↔ prescribing patterns; climate ↔ prescribing patterns). Results From 4,247 citations, 28 studies met inclusion criteria. Studies were conducted across multiple regions, most commonly the United States ( n = 6), United Kingdom ( n = 5), Australia ( n = 5), and Canada ( n = 4), with additional single country and multinational collaborations. Clinical domains varied, with the largest representation in anesthesia and perioperative care ( n = 8), followed by pharmacy and pharmacology ( n = 5), primary care ( n = 3), and fewer in other specialties. Studies used single and multi-educational domains, most commonly framework development ( n = 16), followed by curricular integration ( n = 6). Outcomes included reductions in anesthetic or inhaler related emissions, behavior change, knowledge or awareness, attitudes or satisfaction, and identification of barriers and facilitators. Although individual MAMS dyads were frequently examined, no study operationalized all three domains in an integrated bidirectional tri-dyadic manner. Conclusion Existing literature on climate-conscious prescribing education is expanding but remains clinically concentrated and largely conceptual, with limited evaluation of instructional strategies. No study operationalized a fully bidirectional, tri-dyadic approach linking climate change, pharmaceuticals, and prescribing patterns, underscoring the need for integrated, outcomes-oriented frameworks to guide HPE and practice change.